2020
DOI: 10.3989/mc.2020.13318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperatures on the mechanical behaviour of hybrid cement

Abstract: The high-temperature mechanical behaviour of a pre-industrial hybrid alkaline cement (HYC) was studied. The HYC in question contained 30 % Portland clinker and 70 % of a blend of slag, fly ash and a solid activator (mix of alkaline salts with a predominance of Na2SO4). The material was tested during exposure to high temperatures to establish its compressive and bending strength and elastic modulus, as well as fracture toughness, analysed using an innovative methodology to notch the hydrated cement paste specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The binder used in this study was a preindustrial hybrid alkaline cement [30] containing 30% portland clinker + 32.5% ground granulated blast furnace slag (GGBFS) + 32.5% fly ash (FA) + 5% solid Na 2 SO 4 -based activator. The reference was a commercial portland cement (OPC) (CEM I 42.5R).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The binder used in this study was a preindustrial hybrid alkaline cement [30] containing 30% portland clinker + 32.5% ground granulated blast furnace slag (GGBFS) + 32.5% fly ash (FA) + 5% solid Na 2 SO 4 -based activator. The reference was a commercial portland cement (OPC) (CEM I 42.5R).…”
Section: Methodsmentioning
confidence: 99%
“…Cement pastes prepared with distilled water at a water / cement ratio of 0.3 were poured into stainless steel moulds to form 10x10x60 mm 3 prismatic specimens [30], subsequently cured in a climatic chamber at 22 ± 1°C and 95% relative humidity for 20 h [20][21][22]. After demoulding they were stored in the same chamber until 28 d, when they were measured, weighed, and exposed to temperatures of 400°C, 600°C, 800°C or 1000°C for 2 h in a laboratory oven.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many of these binder systems, a careful balance needs to be drawn between adding sufficient alkalis to enable rapid strength development, and avoiding the excessive alkali levels that may lead to efflorescence. Ongoing work to understand the causes and implications of efflorescence in both one-part and two-part AAM binder systems [166][167][168] Further, the cement paste was tested at up to 1000°C, and showed better high-temperature resistance than Portland cement due to the recrystallization of new poorly hydraulic phases, mainly in gehlenite-and rankinite-type phases [170,171]. Velandia et al [172] also demonstrated the production of concretes with good performance using a hybrid fly ash-Portland-Na2SO4 binder, and provided extensive data about the durability performance of these concretes, including correlations between key durability parameters and compressive strength at ages of up to 1 year.…”
Section: One-part Alkali-activated Bindersmentioning
confidence: 99%